One-pot and two-pot methods for chalcone derived pyrimidines synthesis and applications - Farooq, Saba; Zainab, Ngaini (John Wiley & Sons, Inc, 2021)
Chalcone-derived pyrimidine is a well-known heterocyclic compound that is commonly present in ribonucleic acid (RNA) and deoxyribonucleic acid (DNA) bio-isosteres. Pyrimidine derivatives are effective in both the electronic industry and drug industries. This review highlights the synthesis of pyrimidines, namely mono-pyrimidine, bis-pyrimidine, fused pyrimidine, symmetric, and asymmetric pyrimidine via one-pot and two-pot methods. The one-pot method is the direct reaction of amino derivatives with aldehydes and acetophenones, whereas the two-pot method is frequently reported for the synthesis of chalcone before the cyclization to a pyrimidine. This review is important in organic synthesis, particularly in the heterocyclic field, regarding pyrimidines and their significance in therapeutic and electronic industries.